D4.1 - Directory of European Polar Research Funding Programmes - Vancauwenberghe, Maaike; Deleu, Philippe; Ørbæk, Jon Børre; Strobel, Anneli; Biebow, Nicole (Zenodo, 2022)
The “Directory of Polar research funding programmes in Europe” at hand is EU-PolarNet 2´s initial step to improve the coordination and cooperation of national polar funding organisations in Europe. The directory provides an overview about the governance, strategies, and procedures of polar research funding in Europe. Please cite as: EU-PolarNet 2 consortium (2022) Directory of European Polar Research funding programmes (Eds. Vancauwenberghe M, Deleu P, Ørbæk JB, Strobel A, Biebow N). 58 pp. Bremerhaven: Alfred Wegener Institute.